Introduction: Understanding Digital Sphere in the Networked 21st Century - Jin, Dal Yong (Stream: Interdisciplinary Journal of Communication, 2016)
Since the mid-1990s, our society has substantially advanced digital technologies and their continuous and through integration into people's daily lives. In just a couple of decades, our society has gone from being technically primitive to one of the most advanced in the world (Frey, 2015). Digital technologies have consequently expanded the boundaries of our social circles, and new forms of digital technologies, such as social media and digital platforms, have become parts of our cultural activities. In fact, people do not only use social network sites to keep in touch with friends, but also use them to enjoy certain television drams and popular music. Digital technologies have also changed politics as the users are encouraged to tweet, text, or call in to vote for contestants in everything from reality competition shows to matchmaking endeavours-bridging the gap between our entertainment and our own lives. In the networked 21st century, digital technologies and the media are interwoven, and neither can be separated from contemporary society in most developed and developing nations. By tweeting or uploading people's news and images, the circle of communication is wider than ever (McGivern, 2013). Meanwhile, digital technologies have become some of the most significant tools in the global economy due to their roles as new growth engines for the economy and culture.